Analisis Yuridis Pelaksanaan Kontrak Pengadaan Barang Dan Jasa Di Kabupaten Bima: (CASE STUDI OF SURFACE IRRIGATION NETWORK IMPROVEMENT) - Ardy Putra, Ikhlas; H. Djumardin, H. Djumardin (Faculty of Law, University of Mataram, 2024)
The purpose of this study was to find out and understand the implementation of work contracts to improve surface irrigation networks in Bima Regency between providers and PPK and the obstacles faced by the parties in carrying out work contracts to improve surface irrigation networks in Bima Regency. This type of research is Normative-Empirical. The form of procurement of goverment goods/services is contained in Presidensial Regulation No. 12 of 2021 concerning Amendments to Presidensial Regulation No. 16 of 2018 concerning Government Procurement of Goods/Services. Implementation of the contracting agreement for the contruction of irrigation network between the Office of Public Works and Spatial Planning of the Regency Bima CV. Kawuncu there was the problem in the implementation thas was not in accordance with the predetermined time as a result of exceeding the fine limit and unilaterally terminating the agreement.